Crystallographic parameters in geometrically and topologically close-packed superstructures; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Knestaypin E. A. Evgeny; Morozov M. M. Maksim; Potekaev A. Alexandr; Klopotov A. A. Anatoly; Markova T. N. Tatyana; Klopotov V. D. Vladimir Dmitrievich (2014, 2014)
Title screen